2009
DOI: 10.1111/j.1365-2958.2009.06686.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducer responses of BenM, a LysR‐type transcriptional regulator from Acinetobacter baylyi ADP1

Abstract: SummaryBenM and CatM control transcription of a complex regulon for aromatic compound degradation. These Acinetobacter baylyi paralogues belong to the largest family of prokaryotic transcriptional regulators, the LysR-type proteins. Whereas BenM activates transcription synergistically in response to two effectors, benzoate and cis,cis-muconate, CatM responds only to cis,cis-muconate. Here, site-directed mutagenesis was used to determine the physiological significance of an unexpected benzoate-binding pocket in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 41 publications
1
69
0
Order By: Relevance
“…There are also indications of the potential involvement of a third cysteine in peroxide sensing (4). The LysR-type regulator BenM, which controls genes involved in benzoate catabolism, is known to sense two coinducers (cis,cis-muconate and benzoate) that bind to distinct sites on the protein (23). Binding of each ligand singly activates transcription, while simultaneous binding of both coinducers results in a synergistic increase in target gene transcription (11) that is not observed for all BenM target promoters (21).…”
Section: Resultsmentioning
confidence: 99%
“…There are also indications of the potential involvement of a third cysteine in peroxide sensing (4). The LysR-type regulator BenM, which controls genes involved in benzoate catabolism, is known to sense two coinducers (cis,cis-muconate and benzoate) that bind to distinct sites on the protein (23). Binding of each ligand singly activates transcription, while simultaneous binding of both coinducers results in a synergistic increase in target gene transcription (11) that is not observed for all BenM target promoters (21).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IAA degradation cat genes in strain PsJN is associated with a CatR-like regulator (Fig. 1B), similar to CatM and BenM of Bz catabolism (55,56). However, participation by this regulator remains unclear because strain PsJN cat genes are regulated by IacR2 (Fig.…”
Section: Donoso Et Al Applied and Environmental Microbiologymentioning
confidence: 99%
“…On the other hand, the LTTR family is a well-characterized group of transcriptional regulators, highly conserved and ubiquitous among bacteria (51), which have been involved in control of metabolism, cell division, quorum sensing, virulence, motility, and nitrogen fixation, among others (51)(52)(53)(54). A larger subgroup of LTTRs is associated with degradation of aromatic compounds, in which regulators CatM and BenM of Bz catabolism are quite well studied (55,56). It is reported here that the iacR1 and iacR2 genes are essential for P. phytofirmans IAA catabolism, whereas the lack of the iacS gene decreased catabolism of IAA.…”
Section: Figmentioning
confidence: 99%
“…This coinducer binding region comprises two distinct ␣/␤ subdomains, which are connected by two crossover regions that form a hinge or cleft (34). Previous structural studies identified the binding site for the effector lying between these subdomains of CatM and BenM (4,8). The effector binding domain of BenM was determined with and without the cognate effector (8).…”
Section: Alsr Activates Alssd Transcription In Vitromentioning
confidence: 99%